Inhibition of KRAS Gene Using Different Biochemical Active Compounds - Saif Qahtan Salman (Journal of Global Pharma Technology, 2018)
The KRAS gene is classified as a type of genes called oncogenes. In case of mutation oncogenes have an ability to stimulate the proliferation in cells and make them cancerous. The mutation at 12th position changing the existing amino acid to arginine has been reported in lung cancer. KRAS gene expresses a protein that known as KR as which play a role in signaling pathway called RAS/MAPK. The role of the protein is to transfers signals into the nucleus of the cells. Which are responsible of cell growth and proliferation? In this study, Kras protein sequence, stucture and functional analysis were performed. The antioxidants selected for the study are ascorbic acid, 3, 7, dihydroxyflavone, is oflavone and quercetin. The chemical structures of those antioxidants were studied to be used for binding to the mutational site of KRAS. Based on the binding efficiency the best antioxidant which can be used in lung cancer treatment is determined.Keywords: KRAS gene, Kr as protein, Antioxidants, Ascorbic acid, 3, 7, Dihydroxyflavone, Isoflavone, quercetin.